(untitled) (Orfeu, 2020)
While time is always mentioned as an inherent feature of music, space in most of the times is not included as an operatory feature in composition, something that has changed during the 20th Century due to new compositional and theoretical approaches. This article addresses the construction of a digital instrument in Max/MSP malleable to different conditions of sound diffusion and gathering different possibilities of sound synthesis and high-order ambisonics spatialization, searching to integrate the sound spectrum to the spatialization in electroacoustic music (acousmatic or live-electronics) from the projection of partials and/or grains in movement in the diffusion space. In this context, we present the following theoretical background: 1) historical approaches of space in musical composition, mainly in 20th and 21st Centuries; 2) the ambisonics system, and 3) a conceptualization on the undulatory and granular sound models, situating our proposal in the field of musical composition for high density loudspeaker arrays. As a result, I discuss the composition and spatialization tools included in the digital instrument developed, besides the compositional experiment Imagens transdutivas. As a conclusion, we outline some considerations on sound perception in immersive systems from the ideas of movement image and blocks of space-time.